2019
DOI: 10.1155/2019/9896757
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cherries in Reducing Uric Acid and Gout: A Systematic Review

Abstract: Background Previous studies have reported the use of complementary therapies to reduce the risk of gout attacks. In this study, we assessed the effectiveness of cherries in reducing uric acid levels associated with gout. Methods We searched for relevant studies on PubMed, Embase, and the Cochrane Library without restrictions on language from inception until August 15, 2019. The risk of bias was evaluated using the PRISMA statement and checklist, and the methodological quality was assessed using the Cochrane Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
11
0
4
Order By: Relevance
“…To date, there have been multiple narrative reviews exploring the applications of TC and derived dietary supplements for human health ( 40 , 67 ), exercise recovery and performance ( 67 70 ). Furthermore, several systematic reviews have found favorable effects of TC supplementation on systolic blood pressure and systemic markers of inflammation ( 71 ), uric acid and gout ( 72 ) and endurance exercise performance ( 73 ). However, it is hard to compare the dose of bioactive compounds provided across studies since the methods utilized to analyse the composition of the TC supplements provided are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been multiple narrative reviews exploring the applications of TC and derived dietary supplements for human health ( 40 , 67 ), exercise recovery and performance ( 67 70 ). Furthermore, several systematic reviews have found favorable effects of TC supplementation on systolic blood pressure and systemic markers of inflammation ( 71 ), uric acid and gout ( 72 ) and endurance exercise performance ( 73 ). However, it is hard to compare the dose of bioactive compounds provided across studies since the methods utilized to analyse the composition of the TC supplements provided are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology was written based on several studies published ( 5 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…An animal study of 2 weeks showed that tart cherry juice treatment reduced the serum uric acid levels in hyperuricemic rats in a time-dependent manner [ 19 ]. A system review revealed an association between cherry intake and a reduced risk of gout attacks [ 20 ]. These results implied the potential on improving hyperuricemia as well as exhibited a limitation that presents evidence is lacking in hyperuricemia population for a long treatment by tart cherry.…”
Section: Introductionmentioning
confidence: 99%